Agora FADU: An analysis of an expanded concept of infrastructure in the Buenos Aires School of Architecture of the University of Buenos Aires (ARQUISUR Revista, 2019)
The pavilion 3 of the University of Buenos Aires was designed by the architects Caminos and Catalano (1959-1962) and was planned as one of several generic buildings. It was designated the center of the Architecture and Urbanism Faculty (FAU) in 1971, though unfinished. In 1984 with the return of democracy the FAU became the FADU with the incorporation of design courses and enrollment soared with the opening of free and unrestricted admission to public universities in Argentina. This article analyzes the interaction of the building as a singular physical entity and its complementary relational aspects: whereas in the former this study analyzes more deeply possible characteristics from a systematic understanding, the latter investigates the system of twenty six “vertical cátedras” that includes 11,000 architectural students. This research is based on an expanded concept of infrastructure using theories developed in the 1960s and taken up again at the end of the 1990s as in the essay "Field Conditions" by Stan Allen summarized by the author's statement "Form matters, but not so much the forms of things as the forms between things".
Keywords: expanded infrastructure, field conditions, medium